Effects of age and tocotrienol-rich fraction on mitochondrial respiratory complexes in the hippocampus of rats - Tan, Jen Kit; Sakinah Husna Abdul Razak,; Nazirah Ab Rani,; Nur Haleeda Hakimi,; Hanafi Ahmad Damanhuri,; Suzana Makpol,; Wan Zurinah Wan Ngah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Mitochondrial dysfunction is common in the brain with age. Prevention of mitochondrial dysfunction at an early age may protect the brain against neurodegeneration in later life. Tocotrienol-rich fraction (TRF) has been reported to be neuroprotective in old rats, but its effect remains unknown for middle-aged animals. This study aimed to determine the effect of TRF on activities of mitochondrial respiratory chain complexes in the hippocampus of middle-aged rats. Male Sprague Dawley rats were divided into 4 groups: young control (3 months old), adult control (12 months old), adult rats supplemented with palm kernel oil (PKO) as the vehicle, and adult rats supplemented with TRF by gavage at 200 mg/kg body weight/day for 3 months. At the end of the supplementation, activities of complex I, I+III, II, II+III, III, IV, and citrate synthase in the isolated mitochondria of the hippocampus were measured by spectrophotometry. Complex II activity was higher, while citrate synthase activity was lower in adult rats than in young rats. A decrease of citrate synthase activity suggests loss of mitochondrial mass and intactness in the hippocampus at middle age. Interestingly, PKO-treated adult rats had lower complex I and IV activities, but higher complex I+III activity than adult control rats. These findings indicate PKO modulated activities of the complexes. In TRF-treated adult rats, the complex I activity was higher, while the complex IV activity was lower than PKO-treated adult rats. TRF restored the complex I activity and may have the potential to reverse complex I deficiency.